The influence of human milk composition and its microbiome on the gut microecology and early growth and development of preterm infants (the YI study): protocol design and cohort profile - Wang, Xinyue; Feng, Yan; Li, Yilan; Tian, Yuluyuan; Zhang, Simin; Li, Jinglin; Zhang, Jiahui; Liu, Feng; Zhou, Jiahe; Li, Ting; Duan, Sufang; Szeto, Ignatius Man-Yau; et al. (Frontiers in Nutrition, 2025)
IntroductionBreastfeeding can reduce the risk of serious illness in preterm infants. However, the influence of human milk on the gut microecology and early development of preterm infants remains unclear.MethodsThe YI Study is a prospective cohort protocol conducted in China, designed to investigate the dynamic associations among breast milk composition, infant gut microecology, and health from a mother–breastmilk–preterm infant triad perspective. From January 2023 to May 2024, a total of 50 mother–term infant dyads and 35 mother–preterm infant dyads were enrolled and followed up at six timepoints: v1 (0–7 days), v2 (8–14 days), v3 (1 month), v4 (2 months), v5 (4 months), and v6 (6 months). Data collection included questionnaires, anthropometric measurements, and biospecimens. Questionnaires (including birth medical records, environment, feeding practices and illnesses status) and anthropometric measurements were collected at all visits. Biospecimens included paired samples of breast milk and feces were obtained at each visit, and comprehensively analyzed by multi-omics techniques. We also collected heel blood at birth to examine immune status and saliva at the v6 visit to explore the role of its constituents in dietary behaviors.ResultsThe average age of the mothers was 30.9 ± 3.5 years. The median gestational age was 36 (35, 36) weeks in the Preterm Group and 39 (38, 40) weeks in the Term group. The completion rate up to V6 was 82.9% in the Preterm Group and 94% in the Term Group. All samples were collected within the predefined visit windows, with a total of 452 breast milk, 465 infant feces, 227 maternal feces, 49 heel blood and 98 saliva.DiscussionThrough ultra-early, multi-temporal, multi-sample collection, combined with multi-omics technologies, the YI study will provide an opportunity to explore the dynamic association of human milk as a complex biological system with gut microecology and health in preterm infants in depth.